2022
DOI: 10.3389/fnut.2022.1029116
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and gel-forming ability changes of duck myofibrillar protein induced by hydroxyl radical oxidizing systems

Abstract: This paper focuses on the changes of physicochemical properties and gel-forming ability of duck myofibrillar proteins (DMPs) induced using hydroxyl radical oxidizing systems. DMPs were firstly extracted and then oxidized at various H2O2 concentrations (0, 4, 8, and 12 mmol/L) using Fenton reagent (Fe3+-Vc-H2O2) to generate hydroxyl radicals, and the effects of hydroxyl radical oxidation on the physicochemical changes and heat-induced gel-forming capacity of DMPs were analyzed. We observed obvious increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…These unfavorable conditions hinder the retention of water molecules within the gel, leading to a decline in both its texture and WHC. Similarly, Zhu et al ( Zhu et al, 2022 ) demonstrated a significant correlation (P < 0.05) between decreased WHC in thermally-induced gels and the transformation of immobile water into free water.…”
Section: Resultsmentioning
confidence: 73%
“…These unfavorable conditions hinder the retention of water molecules within the gel, leading to a decline in both its texture and WHC. Similarly, Zhu et al ( Zhu et al, 2022 ) demonstrated a significant correlation (P < 0.05) between decreased WHC in thermally-induced gels and the transformation of immobile water into free water.…”
Section: Resultsmentioning
confidence: 73%
“…We revealed that excessive oxidation led to the explicit cross-linking of DMPs, which negatively affected the gel-forming capacities of DMPs by hydroxy radicals and malondialdehyde. However, the moderate oxidation of malondialdehyde was beneficial for improving its gel-forming properties [ 7 , 8 ]. 2,2′-azobis(2-methylpropionamidine) dihydrochloride (AAPH) generates alkylperoxyl radicals upon degradation, which preferentially oxidize their main targets, tryptophan, cysteine, methionine, tyrosine and, to a lesser extent, histidine residues, respectively, thereby causing protein oxidation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%